Exploring markets: Magic the gathering - a trading card game - Daniel Weber (IU Internationale Hochschule, 2021)
Exploring Markets" is planned as a paper series discussing niche markets with interesting characteristics. The paper on hand focuses on the secondary market of the trading card game "Magic the Gathering", in which players play against each other with decks composed of cards they have collected. Recent high-volume trades raise the question if the investment in pop culture collectibles in general and in Magic the Gathering trading cards in particular can be considered as a legitimateand viable investment form. To answer this question, price developments and market characteristics are analyzed. The paper explicitly aims at people that have never heard of Magic the Gathering and are curious about its basic mechanisms and economics.
Keywords: Z19; 650; Market Study; Trading Card Games; Collectibles